Perancangan Standar Prosedur Operasional (SPO) Pelaksanaan Kegiatan Pendaftaran Klinik - Adhe Irma Ayuningtyas; Arif Nugroho Triutomo; Margono Margono (Journal of Health Information Management and Medical Record, 2025)
Yogyakarta Ministry of Health's Pratama Poltekkes Clinic, especially the Patient Registration Unit, does not yet have Standard Operational Procedures (SPO) for patient registration. The absence of Standard Operational Procedures (SPO) for patient registration has of course caused patient queues, long waiting times and unclear information at the Yogyakarta Ministry of Health's Pratama Poltekkes Clinic. Designing and Designing Standard Operating Procedures (SPO) for Patient Registration at the Pratama Clinic Poltekkes Kemenkes Yogyakarta using the Borg and Gall development stage method, by adopting only the initial 5 stages. This research produced 5 Standard Operational Procedures (SPO) and conducted trials at the Pratama Polytechnic Clinic, Ministry of Health, Yogyakarta with the subject of 2 registration officers and the object of Standard Operating Procedures (SPO) for patient registration at the Pratama Poltekkes Clinic, Ministry of Health, Yogyakarta and the results of the SPO design trial. This research was presented in a qualitative descriptive manner with 3 informants, namely two registration officers in this study and one clinic head as triangulation. Standard Operational Procedures (SPO), which have been tried for 12 days at the Pratama Clinic, Poltekkes Kemenkes Yogyakarta, are running well, can be accepted and well digested by officers. carry out registration activities.